2011
DOI: 10.1021/ja106268w
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Ion Motion in Polymer Light-Emitting Diodes Containing Conjugated Polyelectrolyte Electron Injection Layers

Abstract: The properties and function of an anionic conjugated polyelectrolyte (CPE)-containing ion-conducting polyethylene oxide pendant (PF(PEO)CO(2)Na) as electron injection layers (EILs) in polymer light-emitting diodes (PLEDs) are investigated. A primary goal was to design a CPE structure that would enable acceleration of the device temporal response through facilitation of ion motion. Pristine PLEDs containing PF(PEO)CO(2)Na exhibit luminance response times on the order of tenths of seconds. This delay is attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 78 publications
5
68
0
Order By: Relevance
“…In a series of earlier reports it has been shown that the transient response of mobile ion possessing CPE-based PLEDs is strongly dependent on the ion size and environment (including neighboring functional groups). 9,12,13,19,29,31 The striking difference here between F8im-Br and F8imBT-Br which possess the same mobile bromide ion and imidazolium side chain tethered ionic groups represents a significant deviation from typical behavior. The low electron injection barrier for F8imBT-Br in contact with the Al electrode might also contribute to the fast transient response observed by minimizing the field dropped across the EIL.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In a series of earlier reports it has been shown that the transient response of mobile ion possessing CPE-based PLEDs is strongly dependent on the ion size and environment (including neighboring functional groups). 9,12,13,19,29,31 The striking difference here between F8im-Br and F8imBT-Br which possess the same mobile bromide ion and imidazolium side chain tethered ionic groups represents a significant deviation from typical behavior. The low electron injection barrier for F8imBT-Br in contact with the Al electrode might also contribute to the fast transient response observed by minimizing the field dropped across the EIL.…”
Section: Resultsmentioning
confidence: 92%
“…The initial spike seen for the EL transient in F8im-Br/Al devices has been observed for other PLEDs with polyelectrolyte EILs and is generally attributed to ion rearrangement under the applied electric field. 19,29 The delay (t d ) and rise time (t r ) values (see Figure S9) for the appearance and growth in PLED EL intensity for different EIL devices are summarized in Table 1. The delay time is the time between the on-set of the voltage pulse and the initial rise in EL signal (estimated from the intercept between tangents to the rising EL slope and the EL baseline).…”
Section: Resultsmentioning
confidence: 99%
“…Another possible strategy to overcome this problem would be if the ions could be ''locked'' at one interface after being moved to the emissive layer interface by an applied electrical field. In a paper by Garcia et al [21] an anionic polyelectrolyte containing ionconducting polyethyleneoxide (PEO) units, PF PEO CO 2 Na, was synthesized ( Figure 10.12). PEO units have been shown to facilitate ion transport leading to increased ionic conductivities [22] and have been implemented in LECs [23] and solid-state batteries [24].…”
Section: Improving the Turn-on Time Of Multilayer Pleds Using Cpe Elementioning
confidence: 99%
“…Consequently much effort has been invested in tailoring electrodes using interlayers to optimize charge injection/extraction. [4][5][6][7][8][9][10][11] Recent reports have demonstrated that conjugated electrolytes (CEs) containing a -delocalized backbone and pendant ionic groups are very efficient charge injection/extraction interlayers for device operation, [12][13][14] as they can effectively tune the work function of metal electrodes. [12,15] Furthermore, the ionic groups render the CEs soluble in polar solvents, allowing the subsequent coating process of the organic layer with no damage to or intermixing with the underlying semiconducting polymer layer that typically is deposited with non-polar solvents.…”
Section: Introductionmentioning
confidence: 99%